행성 근접 통과를 이용한 목성 탐사선의 최적 발사 시기 - 송영주; 유성문; 박은서; 박상영; 최규홍; 윤재철; 임조령; 김방엽; 김한돌; 최준민; 김병교; Yoing-Joo Song; et al. (Journal of astronomy and space sciences, 2004)
Interplanetary trajectories using the gravity assists are studied for future Korean interplanetary missions. Verifications of the developed softwares and results were performed by comparing data from ESA's Mars Express mission and previous results. Among the Jupiter exploration mission scenarios, multi-planet gravity assist mission to Jupiter (Earth-Mars-Earth-Jupiter Gravity Assist, EMEJGA trajectory) requires minimum launch energy $(C_3)$ of 29.231 ${\rm km^2/s^2}$ with 4.6 years flight times. Others, such as direct mission and single-planet(Mars) gravity assist mission, requires launch energy $(C_3)$ of 75.656 ${\rm km^2/s^2}$ with 2.98 years flight times and 63.590 ${\rm km^2/s^2}$ with 2.33 years flight times, respectively. These results show that the planetary gravity assists can reduce launch energy, while EMEJGA trajectory requires the longer flight time than the other missions. KCI Citation Count: 2